1976
DOI: 10.1161/01.str.7.6.599
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of cerebrovascular disease in Japanese rural communities, Akabane and Asahi. Part 1: evaluation of risk factors in the occurrence of cerebral hemorrhage and thrombosis.

Abstract: SUMMARY An epidemiological study of cerebrovascular disease in Akabane and Asahi, Japan, was made. (These cities are located near Nagoya, Japan.) The study population included 4,737 men and women aged 40 to 79 at the time of entry into the study. There were 4,186 persons who were examined and, of these, 264 cases of cerebrovascular attacks were observed between 1964 and 1970. The incidence rate of stroke in those persons not responding to the survey was 15.9 times higher than in those persons examined accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
53
2
4

Year Published

1984
1984
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 22 publications
5
53
2
4
Order By: Relevance
“…19 " 21 In the present study the risk of cerebral hemorrhage increased markedly with elevation of both the systolic and the diastolic blood pressure. The results of multivariate analysis also demonstrated that systolic blood pressure was the most important of the various risk factors, followed by diastolic blood pressure.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…19 " 21 In the present study the risk of cerebral hemorrhage increased markedly with elevation of both the systolic and the diastolic blood pressure. The results of multivariate analysis also demonstrated that systolic blood pressure was the most important of the various risk factors, followed by diastolic blood pressure.…”
supporting
confidence: 52%
“…23 In the present study, the risk was high in males in the high and low cholesterol groups and presented a U shape. Okada et al 21 reported similar results. However, on observation by systolic blood pressure level because blood pressure also tended to be high in the high cholesterol group, a tendency was found for the risk to be the higher the lower the cholesterol level in both the low and high blood pressure groups.…”
mentioning
confidence: 56%
“…57 Prior ischemic infarct increases the relative risk of ICH by 5-to 20-fold. [75][76][77] Prior ICH is a risk factor for stroke overall, with a risk of about 1.2% per year for occurrence of either recurrent ICH or ischemic stroke. 77 …”
mentioning
confidence: 99%
“…In Japan, however, some ecological studies compared stroke incidence rates among several defined populations, and showed that the rates were inversely correlated with mean serum cholesterol and fat intake (3,4). Afterwards, some cohort studies indicated that the level of serum cholester ol was inversely associated with the risk of stroke; particularly cerebral hemorrhage and cerebral infarction in perforating artery regions after adjustment for some confounding variables such as sex, age and blood pressure (5)(6)(7).…”
mentioning
confidence: 99%